EFFECTS OF PALM OIL DERIVED TOCOTRIENOL RICH FRACTION AND VITAMIN E ISOMERS ON BIOMARKERS OF EARLY ATHEROGENESIS IN STIMULATED HUMAN UMBILICAL VEIN ENDOTHELIAL CELLS - Suhaila, Abd Muid; Gabriele Ruth Anisah, Froemming; Abd Manaf, Ali; Thuhairah Hasrah, Abdul Rahman; Zalina, Hamid; Hapizah, Nawawi (The Malaysian Society of Applied Biology, 2022)
This study was conducted to investigate the effects of tocotrienol rich fraction (TRF), α-TOC, and pure TCT isomers (α-. γ- & δ-TCT) on inflammation, endothelial activation, nuclear factor kappa B (NFκB), endothelial nitric oxide synthase (eNOS) and monocyte binding activity (MBA) in vitro. Human umbilical vein endothelial cells (HUVECs) were incubated with various concentrations of α-TOC, pure TCT isomers and TRF (0.3-10 µM) together with lipopolysaccharides (LPS) for 16 h. Culture medium and cells were collected and measured for the protein and gene expression of IL-6, TNF-α, NFκB, ICAM-1, VCAM1, e-selectin, and eNOS. Monocyte binding activity (MBA) was measured by Rose Bengal staining. Area under the curve (AUC) analysis revealed that TRF and pure TCT particularly γ- and δ- isomers, showed better inhibition of inflammation and endothelial activation, MBA and greater eNOS increment than α-TOC. These suggest that TRF and pure TCT isomers have potential as preventive anti-atherogenic agents by attenuating the release of early biomarkers of atherogenesis which is better than α-TOC in LPS-stimulated human endothelial cells.